Postgraduate students' accomplishment of epistemic positioning through personal experience in online discussion forums. Issue 1 (2nd January 2020) - Warren, Amber N.; Paulus, Trena M.
ABSTRACT: Few studies have investigated epistemic positioning in online postgraduate courses. Such courses in US contexts rely heavily on asynchronous online discussion forums. This study investigates how postgraduate students' patterned use of personal experience tellings functioned in the construction of their epistemic positioning (as 'expert' or 'novice') as they participated in these forums. Analysis is focused on two patterns observed across the data: (a) making assessments of the course content and activities and (b) engaging in troubles telling. By examining how students' epistemic stance-taking is displayed through these patterned interactions, this study finds that participants' sharing of personal experiences online functions to make visible their epistemic positioning regarding what is treated as 'learnable' in ways that are not possible in face-to-face classrooms. These findings have relevance for what counts as valuable ways of participating in online educational discussions.